A review of modelling languages for adventure educational games - Zahari, A.S. (Institute of Electrical and Electronics Engineers Inc., 2016)
The development of educational games is expensive as educational games are complex programs. Modelling is a known method to handle the complexity of educational games and reduce development cost via automatic code generation. This paper reviews several modelling languages for modelling educational games under the adventure genre. The objective of the review is to assess the coverage of these modelling languages against known adventure genre and flow theory concepts. The assessment result shows that existing modelling languages do not cover all concepts in the adventure genre and flow theory. The effect of not covering these concepts towards game development and game effectiveness as a learning tool are also discussed. Â© 2016 IEEE.